Out of the mainstream : helping the children of parents with a mental illness - Loshak, Rosemary (Abingdon, Oxon : Routledge, 2013)
'Out of the Mainstream identifies those aspects of mental illness which can compromise parenting and affect children's development, as well as the efforts of professionals to intervene effectively. With chapters from professionals working primarily with children or adults, in different agencies and in specialist teams or in the community, the book illustrates the ways in which the needs of mentally ill parents and their children can be understood. The book outlines different theoretical approaches which may be in use alongside each other, including: A systems theory approach to work with families and with agencies ; The psychoanalytic understanding of mental illness and its impact on family relationships and organisations ; An educational approach to supporting staff, children and parents ; A psychiatric or bio-medical model of work. Out of the Mainstream considers how the diverse groups of agencies, specialist teams and groups in the community can work together, even when many barriers may hinder the effective co- working between individuals and these various groups. It will be an invaluable resource for psychologists, psychiatrists, social workers, health visitors, mental health nurses, teachers and voluntary sector agency staff.'--Publisher's website.
Part I: Themes, theories and background -- 1. Hidden children / Rosemary Loshak -- 2. Living with a parent with mental health needs : what children say / Cassie Bromley, Liana Hadleigh and Amy Roe -- 3. Becoming visible: the impact of parental mental health difficulties on children / Lizette Nolte -- 4. Working with the impossible / Rosemary Loshak -- 5. Loss and change in the setting: the demographic, legislative and organisational context / Rosemary Loshak -- Part II: The Children and Adult Mental Health Project (CHAMP) 2002-2012 -- 6. Making a difference : the role of the coordinator / Rosemary Loshak -- 7. Perinatal Crisis Service : psychotherapeutic work with babies and their families at a time of crisis / Sandra Nathanson -- 8. The children's specialist in the adult mental health team / Rosemary Loshak -- 9. How systemic work can contribute towards the development of collaborative work between child and adult mental health services / Philip Messent and Noah Solarin -- 10. A specialist teacher in the Children and Adult Mental Health Project: the growth of an idea / Louise Gallagher and Peggy Gosling -- Part III: The wider context -- 11. Providing a comprehensive service : a partnership with the voluntary sector / Catriona Scott -- 12. Parental mental illness : the adult psychiatrist's perspective and role / Eleni Palazidou -- 13. Managing post-partum depression in the community : who cares for the babies? / Cathy Urwin -- 14. Reflections : what does the future hold for the Children and Adult Mental Health Project? -- Appendix : Origins of CHAMP.
Includes bibliographical references and index.
Keywords: Psychiatric social work; Children of the mentally ill -- Services for; Mentally ill -- Services for; Parents with mental disabilities -- Services for